2015
DOI: 10.1242/jcs.167858
|View full text |Cite
|
Sign up to set email alerts
|

GSTO1-1 modulates metabolism in macrophages activated through the LPS and TLR4 pathway

Abstract: Macrophages mediate innate immune responses that recognise foreign pathogens, and bacterial lipopolysaccharide (LPS) recruits a signalling pathway through Toll-like receptor 4 (TLR4) to induce pro-inflammatory cytokines and reactive oxygen species (ROS). LPS activation also skews the metabolism of macrophages towards a glycolytic phenotype. Here, we demonstrate that the LPS-triggered glycolytic switch is significantly attenuated in macrophages deficient for glutathione transferase omega-1 (GSTO1, note that GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 38 publications
2
48
0
Order By: Relevance
“…[3233] However, LPS itself is a high potent agonist of TLR4 which is apt to confound the interpretation of the subsequent inflammatory pathway. [3435] In 1983, Emancipator et al . [36] for the first time made IgAN models with BALB/c mice by orally immunizing BGG.…”
Section: Discussionmentioning
confidence: 99%
“…[3233] However, LPS itself is a high potent agonist of TLR4 which is apt to confound the interpretation of the subsequent inflammatory pathway. [3435] In 1983, Emancipator et al . [36] for the first time made IgAN models with BALB/c mice by orally immunizing BGG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the evidence that the cell numbers, morphology, and innate immunity functions of resident peritoneal macrophages were significantly altered in mice with long‐term T2D . Noteworthy, the interaction of LPS with Toll‐like receptor 4 (TLR4) was the important inducer of macrophages activation driving inflammatory responses forward . And it has been reported that siRNA‐mediated downregulation of TLR4 leads to reduced LPS sensitivity and suppressed cytokine production .…”
Section: Introductionmentioning
confidence: 99%
“…[14] Noteworthy, the interaction of LPS with Toll-like receptor 4 (TLR4) was the important inducer of macrophages activation driving inflammatory responses forward. [15] And it has been reported that siRNA-mediated downregulation of TLR4 leads to reduced LPS sensitivity and suppressed cytokine production. [16] However, the potential molecular mechanisms for macrophages activation after LPS challenge in T2D have yet to be fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuboi et al were looking for specific inhibitors of human GSTO1‐1 as it had been reported that GSTO1‐1 was overexpressed in human cancer cell lines showing enhanced aggressiveness . In subsequent studies with human GSTO1‐1 knockdown and the ML175 inhibitor, Menon et al showed that human GSTO1‐1 can regulate the oxidative stress and inflammatory response in macrophages through the TLR4 pathway . As these studies were performed in professional immune cells, the question arose of whether human GSTO1‐1 would function in neuronal innate immune pathways, such as in Parkinson disease model cell lines, because previous studies show that neuronal cells possess innate immune pathways mediated through TLR4, although there are cell specific differences observed …”
Section: Resultsmentioning
confidence: 99%